Karakteristik Kawasan Wisata Dengan Metode Deskriptif Kualitatif Berdasarkan Komponen Pariwisata 5A Untuk Meningkatkan Kualitas Pelayanan Pariwisata Di Kebun Binatang Semarang Zoo - Harjanti, Intan Muning; Syafei, Wahyul A.; Sumardi, Sumardi; Chrishelly, Natasya (Badan Riset dan Inovasi Daerah Kota Semarang, 2025)
The tourism sector can be a powerful tool for poverty reduction, job creation, increased government revenue, and infrastructure development. However, effective planning and management are essential to realize these benefits. This study aims to identify the characteristics of the 5A tourism components (Attraction, Activity, Accessibility, Amenities, and Ancillary services) in the Semarang Zoo. A qualitative descriptive research method was employed to analyze these components, by utilized SWOT analysis. The findings indicate that Semarang Zoo generally exhibits strong 5A characteristics. This is evident in the variety of tourist attractions, diverse activities, easy accessibility, comprehensive amenities, and attractive supporting services. Nonetheless, there remains a need for additional attractions and amenities, such as souvenir shops, to further enhance tourist visitation. The results of this study can utilized to improve the quality of tourism services at Semarang Zoo.Â Keywords:Â Tourism; Tourism Components 5A; Attraction; Activity; Accessibility; Amenities; Ancillary Services; Semarang Zoo